1991
DOI: 10.1007/bf00166403
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of individual neighbors by song in the song sparrow, a species with song repertoires

Abstract: Previous theory and research have suggested that bird species with song repertoires in general, and song sparrows (Melospiza melodia) in particular, cannot readily discriminate between the songs of neighbors and strangers. In a recent study (Stoddard et al. 1991) we showed that song sparrows can in fact discriminate neighbors from strangers on the basis of song. In this study we sought to demonstrate that song sparrows can make the finer discrimination between individual neighbors and that they can do so on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(99 citation statements)
references
References 18 publications
6
93
0
Order By: Relevance
“…However, direct contact with the audience may not be necessary for the audience to be apparent. For example, chemical cues from another male induce changes in the courtship displays of male newts (Lissotriton boscai; Aragón, 2009), birds robustly respond to playbacks of conspecific vocalizations (Stoddard et al, 1991(Stoddard et al, , 1988, and humans behave more generously in an economic game when shown stylized visual cues of an observer (Haley and Fessler, 2005). In our experiments we replaced a male audience with male odor (urine or body odor), playbacks of male USVs or an anesthetized male (mixture of tactile and body odor cues) to test whether any of these cues are sufficient to produce an audience effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct contact with the audience may not be necessary for the audience to be apparent. For example, chemical cues from another male induce changes in the courtship displays of male newts (Lissotriton boscai; Aragón, 2009), birds robustly respond to playbacks of conspecific vocalizations (Stoddard et al, 1991(Stoddard et al, , 1988, and humans behave more generously in an economic game when shown stylized visual cues of an observer (Haley and Fessler, 2005). In our experiments we replaced a male audience with male odor (urine or body odor), playbacks of male USVs or an anesthetized male (mixture of tactile and body odor cues) to test whether any of these cues are sufficient to produce an audience effect.…”
Section: Discussionmentioning
confidence: 99%
“…This held true even when the probe songs were much louder than the training stimuli (while still within naturalistic sound levels) and belies the simple idea that birds automatically generalize singer identity across volumes. One possible explanation for this finding lies in the role of intensity cues in behavior: studies in the field have shown that male birds respond differently to playback of a neighbor's song from different distances and positions (Brooks and Falls 1975a;Naguib and Todt 1998;Stoddard et al 1991). Our training set contained only songs recorded over a relatively narrow range of distances-those a male could reach within a standard laboratory cage.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that interactions were simulated outside the territory of the focal male (i.e. a centre^edge e¡ect, see Stoddard et al 1991); indeed, levels of approach and post-playback song were lower during the interaction playback than during the assay playback.…”
Section: Discussionmentioning
confidence: 99%